The Look of Another Mind - Parrott, M (Oxford University Press, 2017)
According to the perceptual model, our knowledge of others' minds is a form of perceptual knowledge. We know, for example, that Jones is angry because we can literally see that he is. In this essay, I argue that mental states do not have the kind of distinctive looks that could sufficiently justify perceptual knowledge of others’ mentality. I present a puzzle that can arise with respect to mental states that I claim does not arise for non-mental properties like being an apple and argue that this is explained by the fact that the looks of non-mental properties adhere to a certain explanatory principle that does not hold for mental states. This shows, I argue, that, even if we think mental states do have looks, these cannot offer sufficient grounds for perceptual knowledge of others' minds. In the final section of the essay, I suggest an alternative way of thinking about our knowledge of others' minds and about the sorts of looks or appearances that might be associated with mental states.